Development and Research of Fatigue Life Testing Device for Robot Reducer - Man Cheng; Cheng Qiu; Jinfeng Li; Jincai Zhang; Wang Zhang; Nan Feng; Xianjin Shi (Jixie chuandong)
Aiming to the demand for the fatigue life test of robot reducer， based on the fatigue life test method， a fatigue life test device is developed. The key parts of the test device are analyzed， and the test verification is carried out. Compared with the continuous rotary fatigue life test device， the test device adopts the inertia load of reciprocating swing， the actual working condition of the robot can be simulated， accelerated fatigue life of the precision reducer can be conducted efficiently and accurately， and the test precision is high， cost is low.